UPAYA MENINGKATKAN KOSA KATA PADA ANAK USIA DINI MELALUI MEDIA BUKU BERGAMBAR - Wulan Dari, Ratna; Sulaeman, Devi; Riyadi, Ahmad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The implementation of technology-based learning is a crucial need to meet the demands of 21st-century skills, especially for elementary school-aged children who are required to have digital literacy, communication, collaboration, creativity, and critical thinking skills. As the educational paradigm shifts in the digital era, innovative learning models are needed to address the challenges of the times and optimize students' potential. The purpose of this study is to describe the process of implementing technology-based learning and analyze its contribution to developing 21st-century skills. This study used a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with teachers and students, and document analysis related to the learning implementation. The results show that the implementation of technology-based learning in the school was able to improve students' digital literacy skills, teamwork, and critical thinking abilities. Teachers acted as facilitators who encouraged exploration, while students demonstrated increased learning motivation and active participation. This implementation also fostered independent learning habits and productive use of technology. The implications of this study emphasize that technology integration not only enriches learning strategies but also serves as an important foundation in shaping a generation that is adaptive, creative, and ready to face global challenges.